Deletion of the Pro-Apoptotic Endoplasmic Reticulum Stress Response Effector CHOP Does Not Result in Improved Locomotor Function after Severe Contusive Spinal Cord Injury - Ohri, Sujata Saraswat (Mary Ann Liebert, Inc., 2012)
Manipulation of various components of the endoplasmic reticulum (ER) stress response (ERSR) has led to functional recovery in diabetes, cancer, and several neurodegenerative diseases, indicating its use as a potential therapeutic intervention. One of the downstream pro-apoptotic transcription factors activated by the ERSR is CCAAT enhancer binding protein (C/EBP) homologous protein (CHOP). Recently, we showed significant recovery in hindlimb locomotion function after moderate contusive spinal cord injury (SCI) in mice null for CHOP. However, more than 40% of human SCI are complete. Thus the present study examined the potential therapeutic modulation of CHOP in a more severe SCI injury. Contused wild-type spinal cords showed a rapid activation of PERK, ATF6, and IRE-1, the three arms of the ERSR signaling pathway, specifically at the injury epicenter. Confocal images of phosphorylated EIF2α, GRP78, CHOP, ATF4, and GADD34 localized the activation of the ERSR in neurons and oligodendrocytes at the injury epicenter. To directly determine the role of CHOP, wild-type and CHOP-null mice with severe contusive SCI were analyzed for improvement in hindlimb locomotion. Despite the loss of CHOP, the other effectors in the ERSR pathway were significantly increased beyond that observed previously with moderate injury. Concomitantly, Basso Mouse Scale (BMS) scores and white matter sparing between the wild-type and CHOP-null mice revealed no significant differences. Given the complex pathophysiology of severe SCI, ablation of CHOP alone is not sufficient to rescue functional deficits. These data raise the caution that injury severity may be a key variable in attempting to translate preclinical therapies to clinical practice.